Urban morphology and climate: field assessment and numerical modeling of interactions. - Pacifici, Martina (2019)
In last decades, the increase of megacities in many regions and particularly in developing countries, contributed to deplete rural landscape enhancing the urbanization impacts. Such urban settlements result in high greenhouse gas emissions and negative energy balances. By gathering millions of people, they develop a complex network of infrastructures, services, housings and factories. Climate impacts of metropolitan areas are universally recognized in the urban heat island (UHI) effect that entails the increase of average night temperatures relative to rural surroundings. New global challenges for urban agendas involve the restraint of urban sprawl, the enhancement of urban density and the mitigation of urban climate changes. Densification strategies had risen as key planning tools to be inserted in the urban development practice. Nevertheless, the integration of compact city pattern into the existing urban structure lead to dense arrangements of urban forms, changes transport models, raises human and energy exchanges, shaping new outdoor environments. In the framework of these transformations, the present work explored the interaction between morphological and climate urban variables in urban lands affected by on-going densification and verticalization processes. An integrated research procedure was developed and applied to a case study in the municipality of São Paulo, characterized by high-rise and low-rise zones under development subjected to a subtropical climate. The proposed procedure integrated field data collections, analysis of database and modeling techniques, addressing multiple scales of analysis. Climate and morphological features were gained by available city database, meteorological stations, Local Climate Zone (LCZ) maps, and further integrated by fieldworks. Numerical models were implemented as interpretation data tools to investigate the physical processes and to build the conceptual model of the interactions between urban morphology and climate. ENVImet and Grasshopper computational codes were used to simulate the existing case study area, as well as to implement numerical experiments (scenarios) in which different densification patterns were tested and compared. The calibration process of the ENVI-met model relied on prior sensitivity tests of input parameters in a smaller domain. Main findings underlined the high-rise buildings shading as the main climate driving force at subtropical latitudes, inducing different microclimates in the outdoor spaces. Compact low-rise areas were found highly affected by high temperatures, low-albedo materials and absence of vegetation. High-rise buildings arrangements were discussed focusing on the effects of buildings heights and spacing variability. Finally, results were summarized in urban design precepts helping climate-sensitive practices and understanding of urban lands in which densification and verticalization processes are in action. Design percepts included suggestions on building height and arrangement, materials and green infrastructure. The importance of a local-scale planning was also highlighted.